The Efficacy Of The Murotal Surah Ar Rahman And The Clitoria Ternatea Plant In Reducing Blood Pressure Levels Among The Elderly Population - Eka RWP Purnamasari; Arif Hidayatullah; Rosario Stephanie F Ornum (CV Media Inti Teknologi, 2025)
The prevalence of hypertension is notably elevated in the aging demographic. A proposed method of reducing blood pressure involves the utilization of non-pharmacological treatment regimens comprising Murottal Surah Ar Rahman and Clitoria Ternatea, as observed in RW 10, located in Paledang, Bogor. This study was conducted from January 30, 2025 to February 5, 2025 in RW 10, Paledang, Bogor. The study's participants included 36 elderly individuals who were prescribed antihypertensive medication. The participants were administered Clitoria Ternatea Linn flower tea and were exposed to Surah Ar-Rahman from the Qur'an (Muslim elderly) as an intervention. The data collection methods employed in this study encompassed the measurement of systolic and diastolic blood pressure prior to and following the intervention. The present study employed a quasi-experimental method, lacking a group control, and utilized a pre- and post-test approach. The findings indicated a substantial variation in systolic blood pressure levels, Surah Ar-Rahman. A decline in systolic pressure from 144 mmHg to 134 mmHg was documented, exhibiting a Z score of -3.726 and a P value less than 0.01, thereby indicating a statistically significant outcome. A decrease in diastolic pressure was also observed, from 91 mmHg to 86 mmHg after the intervention, with a Z score of -2.779 and a P value of 0.005. The administration of Clitoria Ternatea resulted in a decrease in systolic pressure from 141 mmHg to 134 mmHg, while diastolic pressure decreased from 88 mmHg to 87 mmHg. A substantial alteration in systolic pressure was ascertained, with a p-value of less than 0.001. A P-value of 0.310 revealed an absence of correlation between diastolic blood pressure before and after the intervention. The complementary therapy demonstrated efficacy in reducing systolic and diastolic blood pressure. It is imperative to underscore the role of this therapeutic modality as a complementary intervention, not as a primary treatment modality. Hypertension patients are required to take antihypertensive medications and undergo regular checkups as the primary treatment.